1999
DOI: 10.1103/physrevb.60.15488
|View full text |Cite
|
Sign up to set email alerts
|

Exact numerical calculation of the density of states of the fluctuating gap model

Abstract: We develop a powerful numerical algorithm for calculating the density of states ρ(ω) of the fluctuating gap model, which describes the low-energy physics of disordered Peierls and spin-Peierls chains. We obtain ρ(ω) with unprecedented accuracy from the solution of a simple initial value problem for a single Riccati equation. Generating Gaussian disorder with large correlation length ξ by means of a simple Markov process, we present a quantitative study of the behavior of ρ(ω) in the pseudogap regime. In partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 15 publications
2
64
0
Order By: Relevance
“…Its DOS and localization length have a long history of analysis [8,28,29,30]. The spectrum of U , together with the asymptotic behavior of the corresponding eigenstates Ψ z , which as we shall see is determined by b z , have the same information content as the input signal u(t).…”
Section: Introductionmentioning
confidence: 92%
“…Its DOS and localization length have a long history of analysis [8,28,29,30]. The spectrum of U , together with the asymptotic behavior of the corresponding eigenstates Ψ z , which as we shall see is determined by b z , have the same information content as the input signal u(t).…”
Section: Introductionmentioning
confidence: 92%
“…However, Tchernyshyov has pointed out the technical error of the Sadovskii's solution, which is actually an approximation [ 388]. A sophisticated numerical method has shown that the Sadovskii's solution is qualitatively a good approximation for the complex order parameter [ 389,390]; the commensurate CDW is not the case, but the SC is the case. Then, the accuracy of the approximations usable in higher dimensions has been investigated [ 389].…”
Section: Mf Cmentioning
confidence: 99%
“…(15) is correct or not. To clarify this point, we have recently developed an exact numerical algorithm for calculating the DOS of the FGM [8]. For a Gaussian distribution of ∆(x) with zero average and covariance given by Eq.…”
Section: Introductionmentioning
confidence: 99%
“…(5) exactly for a special form of the probability distribution of ∆(x) which is constructed such that its covariance is given by Eq. (8). To begin with, let us perform the following gauge transformation [13],…”
Section: Introductionmentioning
confidence: 99%